Improving Fast Bowling Skills Through Resistance Band Training in Female Cricket Athletes in South Sulawesi - Nurul Utami; Sahabuddin Sahabuddin; M. Adam Mappaompo; Ilham Kamaruddin; Muh. Adnan Hudain (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research is experimental research which aims to determine the improvement of fast bowling skills through resistance band training in female cricket athletes from South Sulawesi. The population in this study were all athletes who took part in training at FIK UNM, with 16 athletes as a sample. The research method used was to provide intervention in the form of resistance band training to 16 people who had been previously measured using a bowling skills test to obtain a pretest. The training intervention was carried out for 16 meetings. After the sample was given intervention, it was measured again using a bowling skills test to obtain post-test data. The data analysis techniques used are descriptive test analysis techniques, data normality tests, and hypothesis testing using SPSS Version 26.00 at a significance level of 95%. Based on the results of the data analysis, it can be concluded that there is an increase in fast bowling skills through resistance band training in female cricket athletes from South Sulawesi. The obtained t-observation value of 17,000 is greater than the t-table value of 2.145 (17,000 > 2.145) with a significant value of 0.000 < α 0.05.